2005
DOI: 10.1038/sj.npp.1300658
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Effects of Repeated Social Defeat Stress on mRNA Expression and Function of μ-Opioid Receptors in the Ventral Tegmental Area of Rats

Abstract: Social defeat stress alters the activity of mesocorticolimbic dopamine projections from the ventral tegmental area (VTA), a process that has been implicated in the development of sensitization and drug-seeking behavior. We showed previously that acute brief social defeat stress increased short-term expression of m-opioid receptor mRNA in the VTA. The present study assessed the presence and functional significance of m-opioid receptor mRNA expression 1 week after the last episode of social defeat stress. Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…For instance, it has been demonstrated that repeated defeated stress or restraint stress increase amphetamine-induced locomotor activity in adult rats (Covington and Miczek 2001;de Jong et al 2005;Nikulina et al 2005;Pacchioni et al 2002). Moreover, an acute cocaine challenge induced a significant increase in locomotor activity in adolescent rats that were previously subjected to restraint stress as compared to the control group (Lepsch et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, it has been demonstrated that repeated defeated stress or restraint stress increase amphetamine-induced locomotor activity in adult rats (Covington and Miczek 2001;de Jong et al 2005;Nikulina et al 2005;Pacchioni et al 2002). Moreover, an acute cocaine challenge induced a significant increase in locomotor activity in adolescent rats that were previously subjected to restraint stress as compared to the control group (Lepsch et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Shaking-crowding consisted of placing 6 rats in a plastic box for 1 hour atop a lab shaker set to generate 220 back-and-forth movements (approximately 2 inch lateral deflection) per min. The resident-intruder social defeat was carried out as described previously (Nikulina et al, 2005; Ruis et al, 1999). Prior to social defeat, the female was removed and the “intruder” Sprague-Dawley rat was introduced into the resident cage.…”
Section: Methodsmentioning
confidence: 99%
“…The shaking-crowding procedure was carried out by placing six rats in a cardboard box atop a lab shaker set to produce 220 back-and-forth movements (approximately 2-inch sideways deflection) per min. The resident-intruder social defeat was performed as described previously (Nikulina et al, 2005;Ruis et al, 1999). The 'intruder' Sprague-Dawley test rat was transported to the Long-Evans residents' housing room.…”
Section: Chronic Unpredictable Stress Proceduresmentioning
confidence: 99%